Telomere Length in Elderly Caucasians Weakly Correlates with Blood Cell Counts. (21st December 2013) - Gutmajster, Ewa; Witecka, Joanna; Wyskida, Magdalena; Koscinska-Marczewska, Justyna; Szwed, Malgorzata; Owczarz, Magdalena; Mossakowska, Malgorzata; Milewicz, Andrzej; Puzianowska-Kuznicka, Monika; Zejda, Jan; Wiecek, Andrzej; Chudek, Jerzy; et al.
Abstract : Background . Age-related decrease in bone marrow erythropoietic capacity is often accompanied by the telomere length shortening in peripheral white blood cells. However, limited and conflicting data hamper the conclusive opinion regarding this relationship. Therefore, the aim of this study was to assess an association between telomere length and peripheral blood cell count parameters in the Polish elderly population. Material and Methods . The substudy included 1573 of 4981 subjects aged 65 years or over, participants of the population-based PolSenior study. High-molecular-weight DNA was isolated from blood mononuclear cells. Telomere length (TL) was measured by QRT-PCR as abundance of telomere template versus a single gene copy encoding acidic ribosomal phosphoprotein P0. Results . Only white blood count (WBC) was significantly different in TL tertile subgroups in all subjects (P = 0.02 ) and in men (P = 0.01 ), but not in women. Merely in men significant but weak positive correlations were found between TL and WBC (r = 0.11, P < 0.05 ) and RBC (r = 0.08, P < 0.05 ). The multiple regression analysis models confirmed a weak, independent contribution of TL to both RBC and WBC. Conclusions . In the elderly, telomere shortening limits hematopoiesis capacity to a very limited extent.